IMPLEMENTASI PENDIDIKAN INKLUSIF DALAM MENINGKATKAN KESAMAAN HAK MEMPEROLEH PENDIDIKAN BAGI SELURUH RAKYAT INDONESIA - Yohana Citra P (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The purpose of writing this work is to know and identify in depth the implementation of inclusive education in Indonesia. Given the progress that has been made in the field of education, there are still several obstacles faced in Indonesia, including unequal access to education, especially in rural areas and remote areas. The preparation of this work uses a library research approach. Literacy reviews from several previous researchers, books, journals and other documents as a reference in criticizing phenomena to collect data. The author in conducting analysis with a descriptive approach. The result of this work is the initial basis for Law Number 20 of 2003 concerning the National Education System, which stipulates that every child has the right to a proper and quality education. The second basis is Law Number 41 of 2007 concerning the Implementation of Inclusive Education. In addition, various education providers take responsibility for the implementation of inclusive education including elements of the government with various supports, school principals with innovation and creation in making policies at the school level, teachers as spearheads when face to face with students and the community as supporters in the implementation of education inclusive.